1999
DOI: 10.1046/j.1365-313x.1999.00496.x
|View full text |Cite
|
Sign up to set email alerts
|

The cell cycle dependent phosphorylation of histone H3 is correlated with the condensation of plant mitotic chromosomes

Abstract: SummaryMitotically dividing cells of Secale cereale, Hordeum vulgare and Vicia faba were studied by indirect immuno¯uorescence using an antibody recognizing phosphorylated histone H3. The study revealed the following features: (i) the H3 phosphorylation starts at prophase and ends at telophase in the pericentromeric chromatin, is associated with the condensation of mitotic chromosomes and is independent of the distribution of late replicating heterochromatin. (ii) Compared with other chromosome regions, the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
2
11

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 21 publications
7
76
2
11
Order By: Relevance
“…There are well-known histone codes for transcriptional silencing and activation and for condensation and decondensation of chromatin. In the case of transcriptional silencing, tri-methylation of K9 and/or K27 on histone H3 is essential (Lachner et al, 2003), and phosphorylation of S10 on this histone is associated with mitotic condensation (Houben et al, 1999). Our findings clearly demonstrate that the acetylation of H4 exhibits residue-, stage-, and chromosome region-specific dynamics during the cell cycle.…”
Section: Discussionmentioning
confidence: 55%
“…There are well-known histone codes for transcriptional silencing and activation and for condensation and decondensation of chromatin. In the case of transcriptional silencing, tri-methylation of K9 and/or K27 on histone H3 is essential (Lachner et al, 2003), and phosphorylation of S10 on this histone is associated with mitotic condensation (Houben et al, 1999). Our findings clearly demonstrate that the acetylation of H4 exhibits residue-, stage-, and chromosome region-specific dynamics during the cell cycle.…”
Section: Discussionmentioning
confidence: 55%
“…A change in H3P distribution on barley chromosomes during mitosis, documented in LM studies (Houben et al, 1999;Manzanero et al, 2002), could be confirmed with indirect immunogold labeling and SEM analysis, revealing a correlation between increasing compaction of chromomeres and increasing signal intensity in the pericentric region. Up to prometaphase, at which stage the chromomeres are still loose and the centromeric constriction is not yet pronounced, H3P signals are evenly distributed on the chromosome (Fig.…”
Section: Chromosomes As a "Loaded Spring"mentioning
confidence: 67%
“…[79][80][81][82] Nonetheless, contradictory conclusions about the relationship between histone H3 phosphorylation and chromosome condensation were obtained in oocytes. Bui et al reported that the changes in histone H3 kinase activity accurately correspond with the phosphorylation of H3/Ser10 and chromosome condensation during porcine oocyte maturation, implicating that H3/Ser10ph is a key event in meiotic chromosome condensation.…”
Section: Functions Of Histone Modifications During Mammalian Oocyte Mmentioning
confidence: 99%